Line-Structured Light-Based Three-Dimensional Reconstruction Measurement System with an Improved Scanning-Direction Calibration Method - Jia Chen; Shantao Ping; Xiaowei Liang; Xulong Ma; Shiyan Pang; Ying He (Remote Sensing)
Three-dimensional (3D) reconstruction measurement technology utilizing line-structured light offers non-contact operation, making it widely applicable in industrial production. An effective scanning-direction calibration method in a line-structured light-based 3D measurement system can not only enhance the system accuracy but also mitigate the production inefficiencies caused by measurement errors. Consequently, developing a high-efficiency and high-precision scanning-direction calibration technique is a pivotal challenge for advancing structured light-based 3D measurement systems. In this study, we propose an improved method to calibrate the sensor’s scanning direction that iteratively optimizes control points via plane transformation while leveraging the rotational invariance of the rotation matrix during translation. By minimizing the reprojection error, an optimized rotation matrix is identified, and the Levenberg–Marquardt (LM) algorithm is subsequently employed to iteratively refine the displacement vector, enabling precise estimation of the scanning direction. Usually, in line-structured light-based 3D reconstruction measurement, a 5 mm standard gauge block is first reconstructed, and then, the reconstruction error of the standard gauge block is used to compare the accuracy of the scanning-direction calibration (other quantities remain unchanged). Hence, we conducted a comparison experiment using the constructed line-structured light-based 3D reconstruction measurement system, and the experimental results demonstrated that the proposed method reduces the reconstruction errors by 29% compared to the classical independent estimation method and by 5% compared to the current joint estimation method. Furthermore, our method eliminates strict distance constraints, thereby enhancing its adaptability in practical applications.